2006
DOI: 10.3748/wjg.v12.i21.3344
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers of human pancreatic adenocarcinomas by expression profiling and validation with gene expression analysis in endoscopic ultrasound-guided fine needle aspiration samples

Abstract: Expression profiling is a useful method to identify biomarkers and potential target genes. Molecular analysis of EUS-guided FNA samples in pancreatic cancer appears as a valuable strategy for the diagnosis of pancreatic adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…182 The genetic profile of EUS-FNA samples has been analyzed through macro-array analysis that included 1,176 genes associated with cancer, by using commercially available complementary DNA samples. 183 A complex statistical analysis was performed (hierarchical clustering, principal component analysis, significance analysis of microarrays) that allowed initial establishment of the gene expression. The results were then validated through quantitative real-time polymerase chain reaction (PCR) and immunohistochemistry.…”
Section: Molecular Markersmentioning
confidence: 99%
“…182 The genetic profile of EUS-FNA samples has been analyzed through macro-array analysis that included 1,176 genes associated with cancer, by using commercially available complementary DNA samples. 183 A complex statistical analysis was performed (hierarchical clustering, principal component analysis, significance analysis of microarrays) that allowed initial establishment of the gene expression. The results were then validated through quantitative real-time polymerase chain reaction (PCR) and immunohistochemistry.…”
Section: Molecular Markersmentioning
confidence: 99%
“…It was first isolated as a 25-kDa glycoprotein covalently bound with matrix metalloproteinase-9 in human neutrophils, and elevated tissue NGAL expression has been documented under diverse infectious and inflammatory conditions, such as inflammatory bowel disease, appendicitis, diverticulitis and urinary tract infections [3]. It has been extensively investigated as a biomarker for the early diagnosis of acute kidney injury from diverse etiologies [4], but recent evidence suggests that NGAL expression is induced in many types of human cancer, including breast [5], gastric [6], esophageal squamous cell [7], colorectal [8], pancreatic [9] and ovarian cancer [10]. In previous work, we have demonstrated that increased levels of NGAL appear to be a characteristic of polycythemia vera and essential thrombocythemia patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…In most of the common human cancers, NGAL expression is upregulated, for example in colorectal cancer, gastric cancer (Kubben et al, 2007), esophageal squamous cell carcinoma (Zhang et al, 2007), lung adenocarcinoma (Friedl et al, 1999), primary liver carcinoma (Li et al, 2012), breast cancer (Fernández et al, 2005), and thyroid neoplasia (Iannetti et al, 2008), while in a few conditions, NGAL expression is downregulated or remains debatable, for example in pancreatic cancer (Furutani et al, 1998;Laurell et al, 2006;Tong et al, 2008), prostate cancer (Mahadevan et al, 2011), and chronic myeloid leukemia (Villalva et al, 2008).…”
Section: Discussionmentioning
confidence: 99%